Pelatihan Menulis Paragraf Deskriptif Memanfaatkan Artificial Intelligence (AI) Bagi Siswa SMKN 1 Jember - Nila Susanti; Cholimatus Zuhro; Agus Setia Budi; Alfi Hidayatu Miqawati; Fitri Wijayanti (Pusat Penelitian Pengabdian Pada Masyarakat Sekolah Tinggi Ilmu Tarbiyah Al-Fattah Siman Lamongan, 2024)
This service aims to increase students' knowledge and skills in writing descriptive paragraphs by using AI in the learning process. The implementation of the service involved 30 students in English lessons by combining several methods, namely lecture, demonstration, simulation, and discussion methods including preparation, implementation, and evaluation stages. The descriptive paragraph writing results of the students before and after the training on the use of Quillbot were evaluated, and with the use of Quillbot, their writing showed improvement in expressing ideas and developing paragraphs logically and systematically, quality in grammatical aspects, and more structured. Questionnaires filled out by participants during the implementation of the activity showed that many students had not utilized Artificial Intelligence so far in any case, especially related to learning activities. Through this training, students have the ability and knowledge from experience in using AI in writing descriptive paragraphs.